Miniaturized Spiral UWB transparent wearable flexible antenna for breast cancer detection - Saeidi, T. (Institute of Electrical and Electronics Engineers Inc., 2020)
A layer of Kapton polyimide with the dielectric constant of 3.5 as substrate and indium tin oxide (ITO) as conductor (10 Ã 10 Ã 0. 375 mm3) are used to construct a miniaturized flexible transparent ultrawideband (UWB) antenna. The antenna's performances are investigated and evaluated using an ITO transparent conductor in both frequency and time domain. The proposed antenna achieves the wide bandwidth (BW) of 3.26-23.37 GHz, more than 65 radiation efficiency for most of the working BW, and maximum radiation efficiency of 90 percent at 15 GHz. Besides, it depicts a stable radiation pattern at most of the operating band and a maximum gain of 3.87 dBi. The good agreement between the simulation and measurement results, time-domain considerations, and the reconstructed image of the tumor makes the antenna capable of working in many applications, especially for breast and skin cancer detection. Â© 2020 IEEE.